Functional morphogenesis from embryos to adults: Late development shapes trophic niche in coral reef damselfishes. Issue 3 (6th December 2019) - James Cooper, W.; VanHall, Rachel; Sweet, Elly; Milewski, Holly; DeLeon, Zoey; Verderber, Amy; DeLeon, Adrian; Galindo, Demi; Lazono, Orissa
Abstract: The damselfishes are one of the dominant coral reef fish lineages. Their ecological diversification has involved repeated transitions between pelagic feeding using fast bites and benthic feeding using forceful bites. A highly‐integrative approach that combined gene expression assays, shape analyses, and high‐speed video analyses was used to examine the development of trophic morphology in embryonic, larval, juvenile, and adult damselfishes. The anatomical characters that distinguish pelagic‐feeding and benthic‐feeding species do not appear until after larval development. Neither patterns of embryonic jaw morphogenesis, larval skull shapes nor larval bite mechanics significantly distinguished damselfishes from different adult trophic guilds. Analyses of skull shape and feeding performance identified two important transitions in the trophic development of a single species (the orange clownfish; Amphiprion percula ): (a) a pronounced transformation in feeding mechanics during metamorphosis; and (b) more protracted cranial remodeling over the course of juvenile development. The results of this study indicate that changes in postlarval morphogenesis have played an important role in damselfish evolution. This is likely to be true for other fish lineages, particularly if they consist of marine species, the majority of which have planktonic larvae with different functional requirements for feeding in comparison to their adult forms. Abstract : We show that the determination of adult damselfish trophic niche arises during late development. We demonstrate this using evidence from gene expression labeling, shape analyses, and video feeding studies that examined damselfish embryos, larvae, juveniles, and adults.